Comparative analysis of alveolar preservation using leukocyte-platelet rich fibrin during maxillary canine distalization: A retrospective study (Research, Society and Development, 2024)
Objective: This study evaluated alveolar preservation using leukocyte-platelet rich fibrin (L-PRF) in adult patients, comparing it to control alveoli. Methods: Conducted from 2016 to 2018, the study included 17 adult patients, aged between 20 and 45 years, diagnosed with either Class I or Angle Class II-1 malocclusion. Participants underwent first premolar extractions, with L-PRF treatment applied to one side of their mouth, while the other side served as a control. This retrospective study compared tomography data from these patients, who also underwent maxillary canine retraction. One side of the mouth was treated as an experimental alveolus, preserved with L-PRF, and the other as a control. Data normality was assessed using the Shapiro-Wilk test. The Wilcoxon test was used for group comparisons, and the McNemar test was applied to fenestrations. Results: No statistically significant differences were observed in root length changes and surrounding bone tissue between the two sides (P > 0.05). Conclusion: The study found no significant differences in root length reduction and changes in supporting bone tissue between the experimental and control sides. This suggests that alveolar preservation with L-PRF does not alleviate the deleterious effects observed during maxillary canine distalization.